The expression pattern of two novel cytokines (IL-24 and IL-29) in human fetal membranes - Nace, Judith; Fortunato, Stephen J.; Maul, Holger; Menon, Ramkumar (Journal of perinatal medicine, 2010)
Objective: Interleukin (IL)-24 and -29 are novel cytokines, produced by immune cells in response to microbial antigens. The functions of these cytokines in the reproductive system are unknown. We examined the expression pattern of IL-24 and IL-29 in human fetal membranes from preterm and term births and in in vitro in response to microbial antigens. Methods: Fetal membranes collected from cesarean sections at term (normal, not in labor) were placed in culture for 48 h. These membranes were then stimulated with bacterial lipopolysaccharide (LPS) or viral antigen poly-inosinic and cytidylic acid (polyIC) for an additional 24 h. Amniotic fluids (AF) and fetal membranes were also collected from preterm and term deliveries. IL-24 and IL-29 expressions were studied by RT-PCR. ELISA documented culture media and AF cytokine concentrations. Results: IL-24 and IL-29 expressions were seen in cultured fetal membranes regardless of stimulation. Expressions were also found in preterm and term labor membranes, but not in non-labor tissues at term. IL-24 concentrations were higher after LPS stimulation whereas IL-29 concentrations were higher after polyIC-stimulation. AF analysis did not detect either of the cytokines either preterm or term. Conclusion: This is the first study to report IL-24 and IL-29 expressions in human fetal membranes. Higher concentrations of these cytokines in response to distinct infectious stimuli suggest different pathways for fetal immune response during infection.
Gesehen am 17.05.2023